PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERAWAT PADA RSIA ERIA BUNDA PEKANBARU - Sinaga, Daniel; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This studyuses 3 variables of work environment,organizational commitment and nurse perfomance. The variables of work environment has 2 dimensions, namely physical environment and non physical work environment. The organizations commitment has 3 dimensions namely affective commitment, continuation commitment and normative commitment. The perfomance variables has 4 dimensi namely quantity, quality, timeliness, and coorporative attitude.the sample use are permanent nurse at RSIA Eria Bunda Pekanbaru with 71 respondents. Data obtained from questionnaires and the processed then tested using statustical analysis such as validity test, reability test, simple linear regression, multiple linear regression, determination test (R2), significant individual test (t test) and simultaneous significant test (f test) with using the SPSS program. The results of the study indicate the influence of work environment and organizations commitment to the perfomance of nurses. The better work work environment and organizations comitment then it will increas and good nurse perfomance. The result of the calculation the determination coefficient (R2) obtained the value of R square of 0,557. The meaning is that the contribution of work environment variables and organization commitment to the performance of nurses is 55,7%. Keyword : work enviroment, organization commitment, perfomance.